Cumulative risk for periprosthetic fracture and operative treatment options after revision total hip arthroplasty with a modular and tapered revision device: a consecutive series of 117 cases in a mid-term duration - Bischel, Oliver E.; Jung, Matthias; Pilgrim, Max; Höppchen, Arnold; Böhm, Paul M.; Seeger, Jörn Bengt (Journal of Clinical Medicine, 2025)
Background: Implantation of modularly built-up stems with a tapered and fluted design is currently state of the art in revision total hip arthroplasty (RTHA). Nevertheless, implant-specific major complications like breakage of taper junctions as well as periprosthetic fractures (PPFs) may lead to failure of reconstruction during follow-up. Methods: A cohort of 117 cases receiving femoral RTHA by a modular stem was investigated retrospectively with a mean follow-up of 5.7 (0.5-13.7) years. Cumulative risk and potential factors affecting the occurrence of PPFs were calculated with the Kaplan-Meier method. In addition, cases were presented to discuss operative treatment options. Results: A cumulative risk of PPF of 12.1% (95% CI: 0-24.6%) was calculated at 13.7 years. Female patients had significantly higher risk compared to male patients (0% after 13.5 years for male patients vs. 20.8% (95% CI: 0.5-41.2%) after 13.7 years for female patients; log-rank p = 0.0438) as all five patients sustaining a PPF during follow-up were women. Four fractures were treated by open reduction and internal fixation. Non-union and collapse of the fracture occurred in one patient after closed reduction and internal fixation. Conclusions: Postoperative PPF after femoral revision with a modular stem has shown to be a frequent complication within this mid-term follow-up. Female patients were at a significantly higher risk in this aged cohort, indicating osteoporosis as a risk factor. The surgical treatment of PPF with an integrated long-stemmed prosthesis is challenging and thorough considerations of adequate operative treatment of PPFs are strongly advised in order to limit complication rates.